DISPARITAS DAN KONVERGENSI PERTUMBUHAN EKONOMI ANTAR KABUPATEN DAN KOTA DI PROVINSI NUSA TENGGARA BARAT - Adha, Rishan; Wahyunadi, Wahyunadi (LPPM Universitas Mataram, 2015)
This study aims to determine the level of inequality that exist in the NTB province, how much the tendency of convergence is happening and what factors are influencing the speed of convergence. This research was conducted in the NTB province, the year of the study period is 2003-2012, the method used is panel data , either Common Effect Model, FixedÃ‚Â EffectÃ‚Â ModelÃ‚Â andÃ‚Â RandomÃ‚Â EffectÃ‚Â Model.Ã‚Â TheÃ‚Â resultsÃ‚Â showedÃ‚Â thatÃ‚Â despiteÃ‚Â an increase in inequality shown by Williamson index and Theil's entropy index at each observation period but the results of the convergence analysis show that convergence is exist in NTB Province. By using two models of convergence, the classic convergence of Barro and Sala-i-Martin and the technological convergence of Dowrick and Rogers, it was found that the speed of convergence is different for each models. By using the classical model,Ã‚Â theÃ‚Â speedÃ‚Â ofÃ‚Â convergenceÃ‚Â betweenÃ‚Â 3%Ã‚Â perÃ‚Â year.Ã‚Â ByÃ‚Â usingÃ‚Â theÃ‚Â transferÃ‚Â of technology model, speed of convergence is much faster at 13% per year. Inter-regional differences in the level of technology greatly affect the speed of convergence, if these differences can be overcome then we will get speeds of convergence much faster.